Pneumatic displacement without tissue plasminogen activator in premacular subhyaloid hemorrhage (Medical Journal of Indonesia, 2007)
To assess the efficacy and safety of intravitreal injection of Sulfur Hexafluoride (SF6) gas without the use of tissue Plasminogen Activator (tPA) in premacular Subhyaloid Hemorrhage (SHH), 5 eyes of 5 patients with premacular SHH were enrolled. After performing paracentesis of the anterior chamber, 0.3 ml pure SF6 gas was injected through pars plana with a 30 gauge needle. Facedown position was maintained for 5 days. Subhyaloid Hemorrhage was displaced in 4/5 (80%) eyes with a duration of SHH less than 2 weeks. The pre-injection visual acuity of all 5 eyes was finger counting and improved in 4/5 ( 80% ) eyes within 3 days to 7 days post-injection to 6/20 - 6/6. The underlying disease was hypercoagulation in 1 patient, diabetes mellitus in 2 patients, hypertension in 1 patient and unknown in 1 patient. No complications were encountered. In conclusion, SF6 gas injected into the vitreous without the use of tPA, can displace SHH if performed within 14 days of duration, and results in rapid visual recovery. This procedure is proven to be safe. (Med J Indones 2007; 16:104-7) Keywords: subhyaloid hemorrhage, pneumatic displacement, sulfur hexafluoride gas